2021
DOI: 10.1038/s41598-021-94956-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude integration in the Archerfish

Abstract: We make magnitude-related decisions every day, for example, to choose the shortest queue at the grocery store. When making such decisions, which magnitudes do we consider? The dominant theory suggests that our focus is on numerical quantity, i.e., the number of items in a set. This theory leads to quantity-focused research suggesting that discriminating quantities is automatic, innate, and is the basis for mathematical abilities in humans. Another theory suggests, instead, that non-numerical magnitudes, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…as the numerosity increases, the non-numerical information increases as well). A previous study led by Leibovich-Raveh et al in archerfish ( Leibovich-Raveh et al, 2021 ) aimed to study whether the spontaneous choice for two numerically different groups of dots was influenced by how many physical variables were positively correlating with numerosity. By manipulating the geometry and spatial disposition of the elements, several stimuli with different congruity levels were created, ranging from 1 to 5 (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…as the numerosity increases, the non-numerical information increases as well). A previous study led by Leibovich-Raveh et al in archerfish ( Leibovich-Raveh et al, 2021 ) aimed to study whether the spontaneous choice for two numerically different groups of dots was influenced by how many physical variables were positively correlating with numerosity. By manipulating the geometry and spatial disposition of the elements, several stimuli with different congruity levels were created, ranging from 1 to 5 (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Still, to date, no studies in archerfish have explicitly investigated abstract numerical abilities. Leibovich-Raveh et al, 2021 showed that when archerfish make magnitude-related decisions, their choice is influenced by the non-numerical variables that positively correlate with numerosity; for instance, when exposed to two groups of dots differing in number and continuous physical information, archerfish spontaneously selected the group containing the larger non-numerical magnitudes and smaller numerosity, switching to the larger numerical set when positively correlated with all the non-numerical magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In a magnitude discrimination task between two groups of dots differing in number, archerfish showed that choice for sets with more/less dots was mainly modulated by non-numerical magnitudes (i.e., overall surface, overall perimeter, density, convex hull, average diameter) that positively correlated with number. Fish tended to select the group containing the larger non-numerical magnitudes and smaller quantities of dots, choosing the larger group of dots only when it was positively correlating with all non-numerical magnitudes [ 86 ].…”
Section: Operant Training Proceduresmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 5, 2021. ; https://doi.org/10.1101/2021.10.04.463045 doi: bioRxiv preprint Still, to date, no studies in archerfish have explicitly investigated abstract numerical abilities. Leibovich-Raveh et al [51] and colleagues showed that when archerfish make magnitude-related decisions, their choice is influenced by the non-numerical variables that positively correlate with numerosity; for instance, when exposed to two groups of dots differing in number and continuous physical information, archerfish spontaneously selected the group containing the larger non-numerical magnitudes and smaller numerosity, switching to the larger numerical set when positively correlated with all the non-numerical magnitudes.…”
Section: Numerical Discrimination Seems To Be Supported By An "Approximate Numbermentioning
confidence: 99%